Pengaruh Pelatihan dan Budaya Organisasi Terhadap Kinerja Karyawan PT. Lintas Aman Andalas Medan - Lismayanti Girsang; Zulkarnain Zulkarnain; Isnaniah Isnaniah (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
The research aims to determine whether work training have a significant positive effect on employee performance at PT. Lintas Aman Andalas, whether organizational culture has a significant positive effect on employee performance at PT. Lintas Aman Andalas, whether work training and organizational culture have a significant positive effect on employees performance at PT. Lintas Aman Andalas. This type of research is associative research. The population is employee amounting to 190 people by using sample technique simple random sampling amounted to 129 employees at PT. Lintas Aman Andalas. Data analysis technique in this research is multiple linear regression analysis. The research data is sourced from the primary data and the process of collecting data using interviews and questionnaires. From the result of the research, the result of work training have positive and significant effect on employee performance, where positive is shown with value 3,380 and significant is shown with 0,001 0,05. Organizational culture has a positive significant effect on employee performance where positively indicated by value 2,393 and significant is indicated by 0,018 0,05. Work training and organizational culture have a positive significant effect on work performance where positive is indicated by the value of 9,564 and significantly indicated by 0,000 0,05.